Pengaruh Metode Mind Mapping Terhadap Peningkatan Kemampuan Daya Ingat Anak pada Pembelajaran Quran Hadits di TPQ Amal Ikhlas Kecamatan Percut Sei Tuan - Rahmad Farras Fawwazi; Fauzi Kurniawan (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
This study aims to determine the Effect of Mind Mapping Method on Improving Children's Memory Ability in Learning Qur'an Hadith at TPQ Amal Ikhlas, Percut Sei Tuan District.This research is motivated by the memory ability of students who are assessed as low at TPQ Amal Ikhlas.This research uses descriptive research with a quantitative approach. The sample in this study is 1 class with a total of 14 students who are used as an experimental class. Data collection was carried out by test using SPSS version 23.Data management techniques used validity tests and reliability tests. For the data analysis test, normality and homogeneity tests were used. The results of this study show that the application of the mind mapping method has a significant effect, it is expected that the memory ability of students at TPQ Amal Ikhlas Percut Sei Tuan District.The average post-test ability of students in the test results is higher than before.